Impacto en la implementación del ERP Sap Business one departamento de contabilidad caso de estudio (2021)
The implementation of the ERP SAP Business One system is very important for companies because they help to optimize and automate processes. The easy integration with other ERPs achieving operational efficiency in companies, currently in the In the Colombian market, there are quite a few organizations that converge and launch this ERP. For the Universidad América, this implementation was carried out, resulting in the following: optimization of processes, time, improvements in financial accounting activities, climate organizational and maintaining the continuous operation given the covid-19 health emergency since the financial area was virtualized. As a methodology to evaluate the impact, a MEFI matrix, the personnel directly involved in the process were interviewed identifying strengths compared to the system that was used previously. The different phases of this project suggested by the system provider and finally the benefits of SAP Business One are highlighted as well as its implementation and maintenance costs which is evidenced as a successful project for the University of America Foundatio